Konsekuensi Distorsi Komunikasi dalam Kepemimpinan (Telaah terhadap Narasi Pembantaian Anak-anak oleh Herodes Agung dalam Matius 2:1-18) - Albert Josua P. Maliogha (PAX HUMANA, 2015)
Communication in leadership have strategic role for reach the aim of a leader. But, communication in leadership also able to distorted to be a tool of propaganda wich manipilative to justice a pressure and deadly leadership, in the same time to secure their authority. Thus the practice of turns made by Herod the Great when respons the Christ is born. Feel afraid that political impact of Christ able to disturb his authority and threat his leadership. The Great Herod open communication sphere with the Magi and the Jewish Religious Leaders to know something about Christ. Through an interdisciplinary approach this writing will highlight a distortion of communication which do by The King of Great Herod in the naration of Mattew 2: 1-18 especially in the motive of assumtion frame an communication that although procedurally was hold many part, but ironically precisely a tool to fullFill maintain a political interests by killing innocent children. This writing aims to give illustration about the face of choice of leadership model that despotic which often manipulate communication for leader interests and its implication for leadership. Keywords: communication, distortion of communication, The Great Herod, authority, Children killing.